Synergistic anti-Campylobacter jejuni activity of fluoroquinolone and macrolide antibiotics with phenolic compounds - Oh, Euna; Jeon, Byeonghwa (Frontiers in Microbiology, 2015)
The increasing resistance of Campylobacter to clinically-important antibiotics, such as fluoroquinolones and macrolides, is a serious public health problem. The objective of this study is to investigate synergistic anti-Campylobacter jejuni activity of fluoroquinolones and macrolides in combination with phenolic compounds. Synergistic antimicrobial activity was measured by performing a checkerboard assay with ciprofloxacin and erythromycin in the presence of 21 phenolic compounds. Membrane permeability changes in C. jejuni by phenolic compounds were determined by measuring the level of intracellular uptake of 1-N-phenylnaphthylamine (NPN). Antibiotic accumulation assays were performed to evaluate the level of ciprofloxacin accumulation in C. jejuni. Six phenolic compounds, including p-coumaric acid, sinapic acid, caffeic acid, vanillic acid, gallic acid, and taxifolin, significantly increased the susceptibility to ciprofloxacin and erythromycin in several human and poultry isolates. The synergistic antimicrobial effect was also observed in ciprofloxacin- and erythromycin-resistant C. jejuni strains. The phenolic compounds also substantially increased membrane permeability and antibiotic accumulation in C. jejuni. Interestingly, some phenolic compounds, such as gallic acid and taxifolin, significantly reduced the expression of the CmeABC multidrug efflux pump. Phenolic compounds increased the NPN accumulation in the cmeB mutant, indicating phenolic compounds may affect the membrane permeability. In this study, we successfully demonstrated that combinational treatment of C. jejuni with antibiotics and phenolic compounds synergistically inhibits C. jejuni by impacting both antimicrobial influx and efflux.